2005
DOI: 10.1080/1540496x.2005.11052609
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Workers' Remittances : The Case of Turkey

Abstract: Workers' remittance flows to Turkey have dramatically increased since the 1960s, constituting a significant proportion of imports. The empirical evidence in this paper indicates that black market premium, interest rate differential, inflation rate, growth, home and host country income levels, and periods of military administration in Turkey have significantly affected these flows. Among them, the negatively significant effects of the black market premium, inflation, and a dummy for periods of military administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 22 publications
8
56
3
Order By: Relevance
“…For instance, whilst ElSakka and McNabb (1999), Bouhga-Hagbe (2006), Yang and Choi (2007), and Singh et al (2010) provide evidence on the countercyclical property of remittances, Higgins et al (2004), Aydaş et al (2004) and Adenutsi et al (2012) find that the pattern of remittance flows is procyclical as it tends to rise with increased GDP per capita and higher growth rate in remittance-receiving countries. Sayan (2006) and Adenutsi et al (2011) also find that in most cases remittances are either acyclical or procyclical.…”
Section: Literature Review On Macroeconomic Determinants Of Remittancesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, whilst ElSakka and McNabb (1999), Bouhga-Hagbe (2006), Yang and Choi (2007), and Singh et al (2010) provide evidence on the countercyclical property of remittances, Higgins et al (2004), Aydaş et al (2004) and Adenutsi et al (2012) find that the pattern of remittance flows is procyclical as it tends to rise with increased GDP per capita and higher growth rate in remittance-receiving countries. Sayan (2006) and Adenutsi et al (2011) also find that in most cases remittances are either acyclical or procyclical.…”
Section: Literature Review On Macroeconomic Determinants Of Remittancesmentioning
confidence: 99%
“…Various empirical studies including those of Elbadawi and Rocha (1992), Lianos (1997), Aydaş et al (2004), Freund and Spatafora (2005), Gupta (2005), Schrooten (2005), Vargas-Silva and Huang (2006) and Singh et al (2010) show that size of migrant stock, host-country versus home-country income gap, exchange rate fluctuations, deposit interest rates; political risk, access to international money transfer facilities and the economic conditions in migrant-host countries affect the volume and frequency of remittance flows. As to whether or not a migrant may remit through the formal or an informal money transfer channel, the level of financial development as reflected in the cost of funds transfer, the existence or absence of dual exchange rate at home, availability of financial infrastructure and innovative products, in especially labor-exporting countries, play an important role.…”
Section: Literature Review On Macroeconomic Determinants Of Remittancesmentioning
confidence: 99%
“…Aydas et al (2004) indicated that the black market premium, interest rate differential, inflation rate, growth, home and host country incomes and periods of military regime have significantly affected Turkish remittance flows. Chami, Fullenkamp and Jahjah (2005) found a statistical significant negative relation between the income gap of the recipient country against the US and workers' remittances in percent of GDP.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Another strand of literature, reviewed by Aydas and Metin-Ozcan (2004), has investigated the macroeconomic determinants of remittances. In this paper, this second path is followed in an attempt to better understand how the macroeconomic and political environment affect remittance flows to the countries in the Sub Saharan African Region.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The annual flow of remittances has fluctuated from year to year due to changing variables related to: (1) Turkish economics and politics, (2) TMs themselves, and (3) determinants related to the countries of residence (Köksal 2006). Remittances reached 2.5% of GNP in the 1980s and went down to about 2% in the 1990s as a result of the increase in other income sources such as tourism and exports (Aydas et al 2005). In spite of these fluctuations, Turkey has been one of the top ten recipients of migrant remittances and remittances have continued to play a central role in its economy (Icduygu 2006).…”
Section: Introductionmentioning
confidence: 98%